Netizens’ perspectives on police repression in agrarian conflict within Seruyan, Central Kalimantan - Martinus Edwin Ferdinand Thanos; Agustinus Rusdianto Berto (Jurnal Studi Komunikasi, 2024)
As an agricultural country, Indonesia utilises the land management sector of the community to realise welfare. However, the implementation in the community often causes conflict, as in Seruyan Regency, Central Kalimantan. This research aims to determine how Computer-Mediated Discourse Analysis (CDMA) can show community responses related to conflicts that occur in Bangkal Village, Seruyan Regency, Central Kalimantan. There were five accounts divided into two groups, which dominated and succeeded in providing a stimulus for other social media users to comment on the conflict that occurred. The analysis was conducted using Netlytic with 1074 nodes and 1214 edges. The results of the study found that netizens who commented on KOMPASTV uploads based on context provided views that created their perceptions of the conflict that occurred.